'Sounding to Present Occasions': Andrew Marvell's 'Two Songs at the Marriage of the Lord Fauconberg and the Lady Mary Cromwell'. Issue 2 (11th October 2018) - Faust, Joan
Abstract : Andrew Marvell's 'Two Songs at the Marriage of the Lord Fauconberg and the Lady Mary Cromwell' does not garner the attention of his other political Protectorate poems, particularly 'An Horatian Ode' and 'The First Anniversary'. Perhaps deterred by the obvious patronage aspects of the two poems, the questionable mixture of myth and pastoral, the epithalamium expectations without the epithalamium structure, and the probable musical setting of the work, readers have tended to ignore the companion pieces as flattering attempts to gain patronage. However, a close study of the poems—the imagery, the allegory, and the genres portrayed therein—evidences Marvell's uncanny ability to structure the work conventionally yet subvert the anticipated framework to depict the tensions, conflicts, and contradictions evident in this marriage. Like its two more prominent 'cousin' poems, 'Two Songs' mirrors and analyzes the uncertainties of Cromwell and his government; however, the work surpasses these poems in its ability not only to depict but even to censure these ambiguities by presenting a personal encomium to the Cromwell family as a pastoral masque in dialogue, joining the two poems as a satiric epithalamium that can then 'sound to present occasions' while subtly portraying conflicts in genres, family, social status, and politics, delighting his audience of 'understanders' with 'more remov'd mysteries '. 'Two Songs' deserves a more prominent place in the Marvell canon.